The level of occupational awareness among the twelfth grade students and their parents in the al batinah region, south of the Sultanate of Oman = مستوى الوعي المنهي لدى طلبة الصف الثاني عشر وآبائهم في منطقة الباطنة جنوب بسلطنة عمان - Al-Kindi1, Adil Mohammed; Al-Hidabi, Dawood Abdulmalek Yahya; Al-Riymi, Ahmad Jumaa (Yayıncı OCERINT International Organization Center of Academic Research, 2020)
This quantitative study discussed the level of students' professional awareness. The problem arises from the presence of many factors that affect the student's professional choice, including the student's knowledge of himself and his capabilities and his ability to make a sound professional decision, and his knowledge of rehabilitation institutions, university education and the world of professions. Including what has to do with the surrounding environment, including parents and their professional awareness. So the aim of the study is: To know the level of occupational awareness among the twelfth-grade students and their parents in the Al Batinah region south of the Sultanate of Oman. And reveal the statistically significant differences in occupational awareness between the twelfth-grade students and their parents. Study methodology; I followed the descriptive analytical research methodology. The study population consisted of all 12th graders in the region. They are (6125) male and female students, distributed among (37) schools in six states. The sample consisted of (312) students. The number of males (152) and females (160). These students meet their parents (312). A unified scale for occupational awareness for students and parents was designed, it included (47) items distributed in six areas: the field of vocational guidance activities, the direction towards work, professional inclinations and capabilities, professional decision-making, professional attention, and vocational planning. Statistical treatment: Descriptive analysis, (T) test, and ANOVA (One-Way test) were used. The results showed that the level of students ’professional awareness is higher than the educationally acceptable average, as well as for their parents, and that the levels of students’ professional awareness fields for parents are (6) All of them came above the educationally acceptable average, and the results also showed that there were statistically significant differences in occupational awareness between students and their parents in favor of students.